Sivelestat Sodium Alleviates Ischemia-Reperfusion-Induced Acute Kidney Injury via Suppressing TLR4/Myd88/NF-κB Signaling Pathway in Mice - Wang J; Wu Y; Mao M; Bing H; Sun L; Xu W; Tian W; Xia Z; Jin X; Chu Q (Dove Medical Press, 2024)
Jie Wang,1 Yuanbo Wu,2 Meng Mao,3 Hailong Bing,1 Liwei Sun,1 Wei Xu,1 Wangli Tian,1 Zhengyuan Xia,4,5 Xiaogao Jin,1,6 Qinjun Chu1 1Department of Anesthesiology and Perioperative Medicine, Zhengzhou Central Hospital Affiliated to Zhengzhou University, Zhengzhou, People's Republic of China; 2Department of Anesthesiology, Hubei Cancer Hospital, Wuhan, Hubei, People's Republic of China; 3Center for Advanced Medicine, Zhengzhou Central Hospital Affiliated to Zhengzhou University, Zhengzhou, 450007, People's Republic of China; 4Department of Anesthesiology, The First Affiliated Hospital, Jinan University, Guangzhou, People's Republic of China; 5Department of Anesthesiology, The University of Hong Kong, Hong Kong; 6Department of Anesthesiology, The Second Affiliated Hospital of Guangdong Medical University, Zhanjiang, People's Republic of ChinaCorrespondence: Xiaogao Jin; Qinjun Chu, Email jinxiaoagao@zzu.edu.cn; jimmynetchu@163.comPurpose: We aim to detect the effects of sivelestat on renal ischemia-reperfusion associated with AKI and also explore the underlying mechanism.Materials and Methods: Mice, aged between 8 and 12 weeks, were randomly allocated among four distinct groups, respectively normal saline sham group(C), normal saline surgery group(I), sivelestat (50 mg/kg) sham group(S), sivelestat (50 mg/kg) surgery group(SI) (n=6, each group). In the surgical groups, the renal pedicles of mice were clamped with non-traumatic micro-aneurysm clamps, resulting in ischemia of the kidneys for 45 minutes. This was followed by a period of reperfusion lasting 24 hours. Sham group mice underwent the identical surgery produced without clamping renal pedicles. Mice blood was obtained from eyeballs, and Serum creatinine and blood urea nitrogen levels were measured. After a 24-hour period of reperfusion, the mice were euthanized, and their kidneys were gathered for various analyses, including Western Blot (WB) analysis, RT-PCR, immunofluorescence (IF), hematoxylin and eosin (H&E) staining, and Tunel assay.Results: Pretreatments with sivelestat decreased renal Neutrophil elastase (NE), serum creatinine, and blood urea nitrogen levels after renal ischemia-reperfusion. Sivelestat also reduced histological damage and cell apoptosis in kidneys following ischemia-reperfusion injury (IRI). In addition, the sivelestat administration diminished the levels of mRNA expression of interleukin 6 (IL-6), Macrophage inflammatory protein-2 (MIP-2), monocyte chemoattractant protein-1 (MCP-1), and tumor necrosis factor (TNF)-α in the kidneys during IRI. The kidney tissues of the SI group had significantly mitigated TLR4, Myd88, and NF-κB p-p65 protein expression levels compared to the I group (all P< 0.05).Conclusion: We demonstrated a previously unidentified mechanism that sivelestat effectively attenuates AKI-induced renal dysfunction, possibly through suppressing the TLR4/Myd88/ NF-κB pathway.Keywords: neutrophil elastase, ischemia reperfusion injury, renal dysfunction, inflammation